Effect Of High Strength Concrete On Capacity Of Prestressed Beam For Bridge Construction - Thai, Kim Sing (Universiti Sains Malaysia, 2017)
Prestressed concrete has become an important and commonly used construction method in bridge engineering. Precast prestressed bridge beam has advantage of better cracking and deflection control compared with conventional reinforced concrete, therefore longer span bridge beam can be achieved. The current standard precast prestressed bridge beam produced in precast concrete industry uses normal strength concrete up to 50 MPa. With the advancement of concrete technology, application of high strength concrete in prestressed concrete might able to bring advantage to the industry. This study was carried out to investigate the percentage increase in beam section capacity when prestressed bridge beam is designed with high strength concrete. The effect of high strength concrete on the prestress strands reduction is also examined. A total of 15 standard prestressed bridge beam models consisting of I-beams, Y-beams, M-beams, U-beams, inverted T-beams and PRT-beams with various depth and span have been studied. Design and analysis were carried out according to BS 5400 standard. The stresses in concrete and deflections were checked to comply with the serviceability limit. It is found that high strength concrete is able to increase the moment capacity of prestressed beam. The percentage increase is dependent on the sectional shape and prestress design. However, current standard bridge beam is found unsuitable to be used together with high strength concrete as the current beams are designed for concrete strength up to 50 MPa. The improvement in beam capacity is limited by the stresses in prestress strands. For shear capacity, it was found that the percentage increment is low and negligible. The result showed the same case for the reduction in strand area required where the percentage of reduction in strand area required is limited by the stresses in prestress strands. The beam section and layout of prestressing strands need to be redesigned in order to make full use of the benefit of high strength concrete.